A mobile game to promote ART adherence among adolescents living with HIV in Eswatini: Development and prototype testing of “The Conqueror” - Londiwe D. Hlophe; Peter S. Nyasulu; Constance S. Shumba (PLoS ONE, 2026)
Background In Eswatini, adolescents living with HIV (ALHIV) face disproportionate challenges in achieving optimal anti-retroviral therapy (ART) adherence, as evidenced by a viral load suppression (VLS) of 77.8% among those aged 15–19 years, compared to the 96.2% VLS observed among adults on ART. While mobile phone ownership has surged globally, facilitating the use of mobile phone-based interventions in healthcare, there remains limited evidence on the development and testing of such interventions for improving ART adherence among ALHIV. This study aimed to design a mobile gaming application (app) to promote ART adherence among ALHIV in Eswatini. Methods A systematic, iterative approach involving a multidisciplinary team of researchers, ALHIV, and app developers was adopted in designing, developing, and testing the prototype of “ The Conqueror” game . A total of seven focus group discussion sessions, each comprising 12 participants conveniently sampled from five Teen Clubs in the Hhohho region of Eswatini, were conducted between 27 April and 20 July 2024 to inform the design and development of the mobile game. The usability and acceptability of the game were assessed using self-administered questionnaires among 35 ALHIV, who were not involved in the game development process and were conveniently selected from the Teen Clubs. The qualitative data were analysed thematically, while the quantitative data were analysed descriptively. Results Participants desired mobile games aimed at enhancing social support through reminders, acceptance, encouragement, and knowledge. Social support was integrated into a storyline that informed the development of The Conqueror , which centres on a hero who conquers opposition and collects an artefact daily to maintain viral suppression. The game features gamification elements such as a life bar, progressive difficulty, daily cycles, three stages with five-day challenges, and power-ups for health boosts and speed increases. The feasibility of The Conqueror were rated relatively high, at 86.2% and 82.8%, for usability and acceptability respectively. Conclusion Gamified mHealth interventions co-developed with potential end-users demonstrate high usability and acceptability. However, further piloting of The Conqueror game through randomized trials is essential to evaluate the feasibility and effectiveness of this approach in improving ART adherence among adolescents before broader implementation and scaling to a wider adolescent population.